Optimization of water distribution networks using hybrid BBO-IWO algorithm - Batmaz, Veli; Kayaalp, Necati (Taylor & Francis Ltd, 2023)
Due to the increasing population and the pollution of existing water resources because of various factors, the need for water in the world is increasing. This requires building additional water distribution systems along with rehabilitation of existing systems. The cost of transmission and distribution constitutes more than half of the total cost of water supply systems. For this reason, by the optimum design of pipeline systems, the cost of water supply can be reduced. In this study, the optimization of pipe diameters in three networks, Two- Loop, Hanoi and GoYang, was carried out by a combination of two metaheuristic algorithms, namely Biogeography based optimization (BBO) and invasive weed optimization (IWO) under the same constraints. In addition, the Combined Gravity Network was successfully optimized with the current method for the first time in the literature.
Keywords: EPANET-MATLAB toolkit; water distribution networks; optimization; BBO algorithm; IWO algorithm